(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
African – American women novelists give voice to the black women who are oppressed,crippled and degraded. A strong believer in the inherent power of women, Alice Walker depicts her titlecharacter Meridian as an innately tough and resolute person, though not one without problems. Thepresent study explains how Meridian tries to establish her identity. She awakens from her subordinatestatus as a black female, daughter, wife and mother to her own self. She realizes that her power lies inher unique and unwavering courage. Meridian features earlier examples of strong female role models.